DPP-4 Inhibitor Teneligliptin Improves Insulin Resistance and Serum Lipid Profile in Japanese Patients with Type 2 Diabetes - Kusunoki, M.; Sato, D.; Nakamura, T.; Oshida, Y.; Tsutsui, H.; Natsume, Y.; Tsutsumi, K.; Miyata, T. (Drug Research, 2015)
Dipeptidyl peptidase-4 (DPP-4) inhibitors have been reported to improve the glycemic control and blood hemoglobin A1c (HbA1c) concentrations. However, there are few reports as yet suggesting that DPP-4 inhibitors may also improve insulin resistance and the serum lipid profile in the clinical setting. This study was aimed at investigating the effect of 14-week treatment with teneligliptin (20 mg/day) on the homeostasis model assessment ratio (HOMA-R), an indicator of insulin resistance, and serum lipid profile in 9 patients with type 2 diabetes. The treatment produced a significant decrease of the blood glucose and HbA1c concentration (blood glucose: p=0.008; HbA1c: p=0.038), and also improved HOMA-R (p=0.039). Furthermore, the patients showed elevation of the serum HDL-cholesterol level (p=0.032), and a tendency towards reduction of the serum triglyceride level. The results indicate that teneligliptin acts not only to improve the blood glucose control, but also to improve the insulin resistance and serum lipid profile in Japanese type 2 diabetes patients.
Keywords: teneligliptin; dipeptidyl peptidase-4 inhibitor; insulin resistance; HDL-cholesterol; triglyceride